De-Islamophobia Melalui Pilar Moderasi Beragama Perspektif Al-Qur’an: De-Islamophobia Through the Pillars of Religious Moderation In the Qur’an Perspective - Febriani, Nur Arfiyah; Badruzaman, Abad (Jurnal Bimas Islam, 2023)
This paper will examine the pillars of religious moderation in the Koran in relation to tackling the problem of Islamophobia both from within and outside of Islam. Searching for the cornerstones of moderation in the Koran uses the thematic method. Namely: First, determining the theme. In this case, is religious moderation. Second: tracing the verses that talk about religious moderation, then drawing several points from it which in the author's observation contain the central teachings (pillars) about religious moderation. Third: each pillar is discussed and developed by referring to relevant references, especially works of interpretation, then contextualized in such a way as to be in line with Indonesian and contemporary dynamics related to efforts to overcome Islamophobia. From the search and discussion of verses related to religious moderation, at least three pillars for religious moderation were found, namely: wasathiyah, samahah, and hiwar.